Predominantly Antibody-Deficient Patients With Non-infectious Complications Have Reduced Naive B, Treg, Th17, and Tfh17 Cells - Edwards, Emily S. J.; Bosco, Julian J.; Aui, Pei M.; Stirling, Robert G.; Cameron, Paul U.; Chatelier, Josh; Hore-Lacy, Fiona; O'Hehir, Robyn E.; van Zelm, Menno C. (Frontiers in Immunology, 2019)
Background: Patients with predominantly antibody deficiency (PAD) suffer from severe and recurrent infections that require lifelong immunoglobulin replacement and prophylactic antibiotic treatment. Disease incidence is estimated to be 1:25,000 worldwide, and up to 68% of patients develop non-infectious complications (NIC) including autoimmunity, which are difficult to treat causing high morbidity and early mortality. Currently, the etiology of NIC is unknown and there are no diagnostic and prognostic markers to identify patients at risk. Objectives: To identify immune cell markers that associate with NIC in PAD patients. Methods: We developed a standardized 11-color flowcytometry panel that was utilized for in-depth analysis of B- and T-cells in 62 adult PAD patients and 59 age-matched controls. Results: Nine males had mutations in BTK and were defined as having X-linked agammaglobulinemia. The remaining 53 patients were not genetically defined and were clinically diagnosed with agammaglobulinemia (n=1), CVID (32), hypogammaglobulinemia (13), IgG subclass deficiency (1) and specific antibody deficiency (6). Of the 53, 30 (57%) had one or more NIC, 24 patients had reduced B-cell numbers and 17 reduced T-cell numbers. Both PAD-NIC and PAD+NIC groups had significantly reduced Ig class-switched memory B cells, and naive CD4 and CD8 T-cell numbers. Naive and IgM memory B cells, Treg, Th17, and Tfh17 cells were specifically reduced in the PAD+NIC group. CD21lo B-cells and Tfh cells were increased in frequencies, but not in absolute numbers in PAD+NIC. Conclusion: The previously reported increased frequencies of CD21lo B cells and Tfh cells are the indirect result of reduced naive B-cell and T-cell numbers. Hence, correct interpretation of immunophenotyping of immunodeficiencies is critically dependent on absolute cell counts. Finally, the defects in naive B- and T-cell numbers suggest a mild combined immunodeficiency in PAD patients with NIC. Together with the reductions in Th17, Treg and Tfh17 numbers, these key differences could be utilized as biomarkers to support definitive diagnosis and to predict for disease progression.